ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS 3 SDN MANGLI 02 JEMBER - Krismawati, Agustin; Arigethi, Vinda Putri; Prayogo, Muhammad Suwignyo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The success of the teaching and learning process is determined by the teaching model, namely the way the teacher conveys the material to be taught. In its truest sense, method means "way". Overall utilization, a model is characterized as an approach to completing an activity or an approach to managing work by utilizing reality and ideas systematically. This research analyzes the problem-based learning (PBL) model in thematic learning. This research was conducted at SDN Mangli 02 Jember. The research method used in this article is descriptive qualitative research. The data collection techniques used by researchers are interviews, observation, and literature study. The data analysis techniques used are based on Miles and Huberman's theory including data collection, data reduction, data presentation, and drawing conclusions. Using the Problem Based Learning method can help to further improve student learning outcomes in Thematic learning. And students easily remember learning material. By implementing the PBL learning model, not all students can understand the material well, for lower classes this model is not suitable because at their age they are still unable to solve a problem given by the teacher.